PENGEMBANGAN MEDIA FUN THINKERS UNTUK MENINGKATKAN LITERSI BERHITUNG SISWA KELAS II UPT SDN TINGKIS - Dea Elisiana; Iis Daniati Fatimah (ELENOR: Elementary School Journal, 2024)
This research uses the type of research and development (R&D). By using the ADDIE (Analysis-Design-Develop-Implementation-Evaluation) model, this research aims to develop Fun Thinkers media to increase the numeracy literacy of class II UPT SDN Tingkis students. The data collection instruments used are observation sheets, interviews, media, material and language validation sheets, teacher and student response questionnaire sheets, and student test widths. The data analysis techniques used are observation and interview data, validity data analysis, practicality data analysis, and effectiveness data analysis. This research resulted in validation results from media experts of 83.15%, material experts of 94%, language experts of 88.89%, so the validity assessment criteria have the "Valid" criteria. It can be concluded that Fun Thinkers media is suitable for use. The results of the teacher response questionnaire scored 98% and the student response questionnaire scored 95%, so the criteria for assessing the practicality of the Fun Thinkers media were declared "Very Practical" for use. The student test results have a classical completion percentage of the student test of 81%, so the Fun Thinkers media is said to be "effective" for increasing students' numeracy literacy and is used in learning. must be written in two languages, Indonesian and English.